Apparently contradictory routes in the expansion of two fish species in the Eastern Atlantic. Issue 4 (2nd March 2020) - Bañón, Rafael; de Carlos, Alejandro; Alonso‐Fernández, Alexandre; Ramos, Fernando; Baldó, Francisco
Abstract: One specimen of the boreal Clupea harengus (Clupeidae) was caught southerly, in the Gulf of Cádiz (southern Spain), whereas a specimen of the subtropical Epinephelus aeneus (Serranidae) was caught northerly, in Galician waters (north‐west of Spain). These catches represent a new southernmost record in the eastern Atlantic for C. harengus and the second northernmost for E. aeneus . The co‐occurrence of warm and cold affinity fishes in temperate latitudes is unusual, but the existence of anomalies in the temperature of the Atlantic waters could be behind these findings.